Market and non-market mechanisms for the optimal allocation of scarce resources - Daniele Condorelli (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2009)
Both market (e.g. auctions) and non-market mechanisms (e.g. lotteries and priority lists) are used to allocate a large amount of scarce public resources that produce large private benefits and small consumption externalities. I study a model in which the use of both market and non-market mechanisms can be rationalized. Agents are risk neutral and heterogeneous in terms of their monetary value for a good and their opportunity cost of money, which are both private information. The designer wants to allocate a set of identical goods to the agents with the highest values. To achieve her goal, she can screen agents on the basis of their observable characteristics, and on the basis of information on their willingness to pay that she can extract using market mechanisms. In contrast to models where willingness to pay and value coincide, a first best cannot be achieved. My main result is that both market and non-market mechanisms, or hybrid mechanisms, can be optimal depending on the prior information available to the designer. In particular, non-market mechanisms may be optimal if the value is positively correlated with the opportunity cost of money.
Keywords: 330